Safety, tolerability, and immunogenicity of a 21-valent pneumococcal conjugate vaccine, V116, in healthy adults: phase 1/2, randomised, double-blind, active comparator-controlled, multicentre, US-based trial. Issue 2 (February 2023) - Platt, Heather; Omole, Tosin; Cardona, Jose; Fraser, Neil J; Mularski, Richard A; Andrews, Charles; Daboul, Nizar; Gallagher, Nancy; Sapre, Aditi; Li, Jianing; Polis, Adam; Fernsler, Doreen; et al.
Summary: Background: A pneumococcal conjugate vaccine (PCV) specifically focused on serotypes associated with adult residual disease burden is urgently needed. We aimed to assess V116, an investigational 21-valent PCV, that contains pneumococcal polysaccharides (PnPs), which account for 74–94% of invasive pneumococcal disease in adults aged 65 years or older. Methods: We did a phase 1/2, randomised, double-blind, active comparator-controlled, multicentre, non-inferiority and superiority trial. The phase 1 study was done at two clinical sites in the USA, and the phase 2 study was done in 18 clinical sites in the USA. Eligible participants were healthy adults with or without chronic medical conditions assessed as stable, aged 18–49 years in the phase 1 trial and aged 50 years or older in the phase 2 trial. Participants were excluded if they had a history of invasive pneumococcal disease or other culture-positive pneumococcal disease within the past 3 years, known hypersensitivity to a vaccine component, known or suspected impairment of immunological function, were pregnant or were breastfeeding, or had previously received any pneumococcal vaccine. Participants had to abstain from sexual activity or use protocol approved contraception. All participants were centrally randomly assigned to a vaccine group using an interactive response technology system. Participants and investigators were masked to group assignment. In phase 1, participants were randomly assigned (1:1:1) to receive a single dose of V116-1 (2 μg per pneumococcal polysaccharide [PnP] per 0·5 mL) or V116-2 (4 μg per PnP per 1·0 mL) or the 23-valent unconjugated PnP vaccine, PPSV23 (25 μg per PnP per 0·5 mL). In phase 2, participants were randomly assigned (1:1) to receive one dose of V116 (4 μg per PnP per 1·0 mL) or PPSV23 (25 μg per PnP per 0·5 mL), stratified by age. Safety analyses included all randomly assigned participants who received study vaccine; immunogenicity analyses were per protocol. For both phases, the primary safety outcome was the proportion of participants with solicited injection-site adverse events and solicited systemic adverse events up to day 5 after vaccination and the proportion of participants with vaccine-related serious adverse events to 6 months after vaccination. In phase 2, primary immunogenicity outcomes were to test non-inferiority of V116 compared with PPSV23 as measured by serotype-specific opsonophagocytic antibody geometric mean titres (OPA-GMT) ratios for the serotypes common to the two vaccines at 30 days after vaccination (using a 0·33 margin) and to test superiority of V116 compared with PPSV23 as measured by serotype-specific OPA-GMT ratios for the serotypes unique to V116 at 30 days after vaccination (using a 1·0 margin). This trial is registered with Clinicaltrials.gov, NCT04168190 . Findings: Between Dec 6 and 26, 2019, 92 volunteers were screened and 90 (98%) enrolled for phase 1 (59 [66%] women; 31 [34%] men); 30 participants were assigned to each group and received study vaccine. 30 (100%) participants in the V116-1 group, 29 (97%) in the V116-2 group, and 30 (100%) participants in the PPSV23 group were included in the per-protocol immunogenicity evaluation. From Sept 23, 2020, to Jan 12, 2021, 527 volunteers were screened, and 510 (97%) participants were enrolled in the phase 2 trial. 508 participants (>99%; 254 [100%] of 254 participants randomly assigned to the V116 group and 254 [99%] of 256 randomly assigned to PPSV23 group) received study vaccine (281 [55%] women; 227 [45%] men). 252 (99%) of 254 of participants in the V116 group and 254 (99%) of 256 participants in the PPSV23 group were included in the primary immunogenicity analyses. There were no vaccine-related serious adverse events or vaccine-related deaths in either study phase. In both phases, the most common solicited injection site adverse event was injection site pain (phase 1 22 [73%] participants in V116-1 group, 23 [77%] participants in V116-2 group, and 17 [57%] participants in the PPSV23 group; phase 2 118 [46%] of 254 participants in the V116 group and 96 [38%] of 254 in the PPSV23 group]. The most common solicited systemic adverse events in phase 1 was fatigue (eight [27%] participants in the V116-1 group, eight [27%] participants in the V116-2 group, and five [17%] participants in PPSV23 group) and myalgia (eight [27%] participants in the V116-1 group, nine (30%) participants in the V116-2 group, and four (13%) participants in the PPSV23 group]. In phase 2, the most frequently reported solicited systemic adverse event was fatigue (49 [19%] participants in V116 group, and 31 [12%] participants in PPSV23 group). In both phases, most of the solicited adverse events in all vaccine groups were mild and of short duration (≤3 days). V116 met non-inferiority criteria compared with PPSV23 for the 12 shared serotypes and met superiority criteria compared to PPSV23 for the nine unique serotypes. Interpretation: V116 was well tolerated with a safety profile generally similar to PPSV23; consistent with licensed pneumococcal conjugate vaccines. Functional OPA antibodies were induced to all V116 vaccine serotypes. The vaccine was non-inferior to PPSV23 for the 12 serotypes common to both vaccines and superior to PPSV23 for the nine unique serotypes in V116. Our findings support the development of V116 for prevention of pneumococcal disease in adults. Funding: Merck Sharp & Dohme, subsidiary of Merck & Co, Rahway, NJ, USA.